New species of Aleurodamaeus Grandjean, 1954 (Oribatida: Aleurodamaeidae) from South Africa - Hugo-Coetzee, Elizabeth A. (Zootaxa, 2013)
Seven new species of Aleurodamaeus (Oribatida: Aleurodamaeidae) from South Africa are described: A. salvadordalii sp. nov., A. vicinus sp. nov., A. angelae sp. nov., A. niedbalai sp. nov., A. minutus sp. nov., A. woasi sp. nov. and A. prominens sp. nov.. Their distribution in South Africa is discussed. Aleurodamaeus deswardti (Hugo, 2010) comb. nov. is proposed. A key to all South African species of Aleurodamaeus is provided.